Nuclear receptors: from molecular mechanisms to therapeutics. Issue 6 (26th November 2021) - Frigo, Daniel E.; Bondesson, Maria; Williams, Cecilia
Abstract: Nuclear receptors are classically defined as ligand-activated transcription factors that regulate key functions in reproduction, development, and physiology. Humans have 48 nuclear receptors, which when dysregulated are often linked to diseases. Because most nuclear receptors can be selectively activated or inactivated by small molecules, they are prominent therapeutic targets. The basic understanding of this family of transcription factors was accelerated in the 1980s upon the cloning of the first hormone receptors. During the next 20 years, a deep understanding of hormone signaling was achieved that has translated to numerous clinical applications, such as the development of standard-of-care endocrine therapies for hormonally driven breast and prostate cancers. A 2004 issue of this journal reviewed progress on elucidating the structures of nuclear receptors and their mechanisms of action. In the current issue, we focus on the broad application of new knowledge in this field for therapy across diverse disease states including cancer, cardiovascular disease, various inflammatory diseases, the aging brain, and COVID-19.